Eco-friendly functional cellulose paper as a fire alarming via wireless warning transmission for indoor fireproofing - Li, Xiaolu; Sánchez Del Río Sáez, José; Vázquez López, Antonio; Ao, Xiang; Sánchez Díaz, Raquel; Wang, De-Yi (My University, 2023)
Herein, a strategy for fabricating wallpaper-based smart fire-warning systems to monitor and mitigate indoor fires is proposed. The fire-warning system, based on eco-friendly cellulose paper (CP), is produced via a simple dip-coating technique and provides flexibility, rapid low-temperature warning, and novel local and remote wireless signal conversion capability. Specifically, this fire-warning system can balance flexibility and flame retardancy, reducing the negative impact on the mechanical properties after adding flame retardants. Furthermore, the proposed fire-warning system meets the critical requirement of a fast low-temperature warning, showing warning messages within 2s under 250º C, decreasing the response temperature below the combustion temperature of common materials (>300º C). Moreover, the luminosity and temperature data collected can be sent to local and remote computers by wireless conversion. This work gives insight into the new generation of low-temperature smart fire-warning systems, including the contribution of wireless warning signal transmission to achieve smart and efficient fire detection.

Herein, a strategy for fabricating wallpaper-based smart fire-warning systems to monitor and mitigate indoor fires is proposed. The fire-warning system, based on eco-friendly cellulose paper (CP), is produced via a simple dip-coating technique and provides flexibility, rapid low-temperature warning, and novel local and remote wireless signal conversion capability. Specifically, this fire-warning system can balance flexibility and flame retardancy, reducing the negative impact on the mechanical properties after adding flame retardants. Furthermore, the proposed fire-warning system meets the critical requirement of a fast low-temperature warning, showing warning messages within 2s under 250º C, decreasing the response temperature below the combustion temperature of common materials (>300º C). Moreover, the luminosity and temperature data collected can be sent to local and remote computers by wireless conversion. This work gives insight into the new generation of low-temperature smart fire-warning systems, including the contribution of wireless warning signal transmission to achieve smart and efficient fire detection.
Artículos en revistas
Keywords: Instituto de Investigación Tecnológica (IIT)